Adenocarcinoma and squamous cell carcinoma in the same lobe of the lung with adenocarcinoma metastasis in the lymph nodes: a case report and literature review - Li, Chun-Sen; Zou, Yun-Xuan; Wang, Chun-Yan; Xu, Guo-Dong; Yang, Mai-Qing (Frontiers in Oncology, 2025)
Adenocarcinoma and squamous cell carcinoma (SCC) of the same lobe of the lung is relatively rare. A 57-year-old man was admitted to Weifang People’s Hospital (Weifang, China) with blood streaks in sputum and had masses in the lung. Based on clinical, imaging, and pathological findings, the patient was diagnosed with primary adenocarcinoma and SCC in the same lobe of the right lung, with adenocarcinoma metastasis to the lymph nodes. Few reports have described the synchronous occurrence of adenocarcinoma and SCC in the same lobe. Thoracoscopic resection of the lower lobes of the right lung and mediastinal lymph node dissection were performed. Surgical resection and postoperative chemotherapy have superior effects. The misdiagnosis of this tumor as other types of tumor must be prevented. Immunohistochemical features can be useful for the diagnosis of primary adenocarcinoma and SCC.